A new member of the psToc159 family contributes to distinct protein targeting pathways in pea chloroplasts - Chang, WaiLing; Soll, Jürgen; Bölter, Bettina (Frontiers in Plant Science, 2014)
Protein import into chloroplasts relies on specific targeting of preproteins from the cytosol to the organelles and coordinated translocation processes across the double envelope membrane. Here, two complex machineries constitute the so called general import pathway, which consists of the TOC and TIC complexes (translocon at the outer envelope of chloroplasts and translocon at the inner envelope of chloroplasts, respectively). The majority of canonical preproteins feature an N-terminal cleavable transit peptide, which is necessary for targeting and recognition at the chloroplast surface by receptors of TOC, where Toc159 acts as the primary contact site. We identified a non-canonical preprotein without the classical transit peptide, the superoxide dismutase (FSD1), which was then used in chemical crosslinking approaches to find new interaction partners at the outer envelope from pea chloroplasts. In this way we could link FSD1 to members of the Toc159 family in pea, namely psToc132 and psToc120. Using deletion mutants as well as a peptide scanning approach we defined regions of the preprotein, which are involved in receptor binding. These are distributed across the entire sequence; however the extreme N-terminus as well as a C-proximal domain turned out to be essential for targeting and import. En route into the plastid FSD1 engages components of the general import pathway, implying that in spite of the non-canonical targeting information and recognition by a specific receptor this preprotein follows a similar way across the envelope as the majority of plastid preproteins.